Kondisi Mental Anak Pascapernikahan-Kembali Ibu Tunggal: Tinjauan Maqashid Syariah - Liddinillah, Muhammad Yakhsyallah; Al-Arif, Muhammad Yasin; Baihaqi, Yusuf (Al-Qisthu, 2024)
The high divorce rate in Indonesia often has a significant impact on the mental well-being of children, particularly due to the absence of a father figure and emotional instability within the family. This study focuses on the impact of single mothers’ remarriage on children’s mental development from the perspective of maqāṣid al-sharīʿah. The primary issue explored is how the presence of a stepfather influences the emotional, social, and intellectual stability of children in post-divorce families. The study employs a qualitative approach with a phenomenological design, involving in-depth interviews with six single mothers who have remarried in Negararatu Village, South Lampung. The findings reveal that the presence of a stepfather positively contributes to the reinforcement of religious values (ḥifẓ ad-dīn), emotional well-being (ḥifẓ an-nafs), intellectual development (ḥifẓ al-‘aql), family relations (ḥifẓ an-naṣl), and economic stability (ḥifẓ al-māl). From the perspective of maqāṣid al-sharīʿah, remarriage not only strengthens family structure but also supports the psychological recovery of children after divorce. The novelty of this study lies in integrating the maqāṣid al-sharīʿah framework with the modern family context to explain the role of stepfathers in enhancing children’s mental well-being holistically.